2021
DOI: 10.1590/1809-4430-eng.agric.v41n5p504-516/2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plastic Mulching and Straw Incorporation on Rice Yield and Nitrogen Use Efficiency in a Cold Region

Abstract: For the synergistic improvement of soil fertility and rice yields in a cold region, we investigated the effects of plastic mulching with different straw incorporation rates on the rice yield and nitrogen use efficiency in a rice growing area of a cold region. The field experiment was conducted using the Jijing 88 rice cultivar, and set up four straw incorporated treatment: 20% (S1), 40% (S2), 60% (S3) and 100% (S4) under two conditions: mulching (M) and without mulching (NM). The results showed that under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…This study showed a significant increase in nitrogen accumulation in both peanut plants and pods with an increase in the nitrogen application rate. Some studies have suggested that when the nitrogen application rate is 225 kg·ha −1 , the nitrogen-use efficiency decreases with an increase in the nitrogen application rate [ 35 ]. The optimal nitrogen application rate was 110 kg·ha −1 in this experiment, and this might be due to different crops.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a significant increase in nitrogen accumulation in both peanut plants and pods with an increase in the nitrogen application rate. Some studies have suggested that when the nitrogen application rate is 225 kg·ha −1 , the nitrogen-use efficiency decreases with an increase in the nitrogen application rate [ 35 ]. The optimal nitrogen application rate was 110 kg·ha −1 in this experiment, and this might be due to different crops.…”
Section: Discussionmentioning
confidence: 99%
“…Rice holds immense significance as a staple food for nearly 50% of the global population [1,2]. However, the productivity of rice cultivation has encountered stagnation in many rice-growing regions [3], largely due to the influence of climatic conditions, field management practices [4], and soil quality [5]. Among these factors, soil quality is shaped not only by soil genesis but also by various factors associated with soil utilization and management [6], including straw incorporation and irrigation regimes [7,8].…”
Section: Introductionmentioning
confidence: 99%